Enhancing domestic revenues to reduce the budget deficit in Saudi Arabia: an empirical study (1992-2020) - Bokhari, Abla Abdulhameed; Halwani, Abrar Adel; Bajaber, Nadia Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
The growing public budget deficit considers as one of the most important challenges facing the Kingdom of Saudi Arabia, as a result of the increase in public spending on the one hand, and the dependence of public revenues on oil on the other. This made diversification of non-oil revenues an urgent requirement to achieve financial balance and economic stability. Hence, this study aims to estimate the impact of domestic revenues on the public budget deficit in the Kingdom of Saudi Arabia during the period from 1992 to 2020. The study follows the descriptive and analytical econometrics approach, to describe the different dimensions of the concerned subject through literature review, then estimating the impact of local revenues on the budget deficit in the Kingdom during the period 1992-2020, using the Autoregressive Distributed Lag (ARDL) model. The results confirmed the existence of cointegration and a long-term equilibrium relationship, in accordance with the assumptions of the study. In particular, an increase in oil and non-oil revenues lead to an increase in the budget surplus (a decline in the budget deficit) by 0.73 and 0.67 unit, respectively. While an increase in total public expenditures by one-unit associates with a reduction in the budget surplus (an increase in the budget deficit) by approximately 0.77 unit. Thus, the study concluded that it is important to utilize oil revenues in high return social infrastructure, while continuing efforts to develop non-oil revenues through non-tax sources, and reconsidering the nature of taxes imposed, such as the adoption of progressive taxes and welfare taxes. It also requires reconsidering some aspects of financial compensation for expatriates and service fees to support the private sector, which is entrusted with bearing the responsibility of contributing to diversification efforts and promoting economic growth.